Oral health care in the 21st century: It is time for the integration of dental and medical education. Issue 9 (20th May 2020) - Donoff, R. Bruce; Daley, George Q.
Abstract: Major issues exist in the provision of oral health care in America, especially to underserved populations. Access to care, health disparities, an aging population with higher chronic disease burden, and rising healthcare costs continue to impact health outcomes for millions. The marginalization of oral health care, like that of behavioral health care, is a contributor. This perspective presents an idea whose time has come: putting the mouth back in the body. Several national reports stress the imperative to better integrate the practice of medicine and dentistry, including the first‐ever Surgeon General's Report on Oral Health in 2000. A plan to lead a multifaceted integration of oral health into overall health is proposed. Leaders will come from new educational and practice models stressing teamwork, interprofessional education, innovative residency training programs and even dual degree options.